Incorporating Equity and Resiliency in Municipal Transportation Planning: Case Study of Mobility Hubs in Oakland, California. Issue 1 (2017) - Anderson, Karl; Blanchard, Samuel D.; Cheah, Derek; Levitt, Drew
This paper presents a multicriteria suitability analysis framework to aid municipal governments in efforts to determine optimal siting of mobility hubs in their jurisdictions. Mobility hubs are agglomerations of transportation modes that concentrate emerging shared mobility services in well-defined locations, delivering several benefits to users. These benefits include primarily increased connectivity among modes and augmentation of public transit with improved first- and last-mile connections. The framework was applied to a case study in Oakland, California. The presented methodology has the potential for broader use by transportation planners and policy makers to advance various qualitative values in their practice, including equity and resiliency, and can quantitatively inform geographic, values-oriented outcomes.